Co-Delivery of 8-Hydroxyquinoline Glycoconjugates and Doxorubicin by Supramolecular Hydrogel Based on α-Cyclodextrin and pH-Responsive Micelles for Enhanced Tumor Treatment - Adrian Domiński; Tomasz Konieczny; Marcin Godzierz; Marta Musioł; Henryk Janeczek; Aleksander Foryś; Monika Domińska; Gabriela Pastuch-Gawołek; Tomasz Piotrowski; Piotr Kurcok (MDPI AG, 2022)
The sustained release of multiple anti-cancer drugs using a single delivery carrier to achieve a synergistic antitumor effect remains challenging in biomaterials and pharmaceutics science. In this study, a supramolecular hydrogel based on the host-guest complexes between pH-responsive micelle derived poly(ethylene glycol) chains and α-cyclodextrin was designed for codelivery of two kinds of anti-cancer agents, hydrophilic 8-hydroxyquinoline glycoconjugate and hydrophobic doxorubicin. The host-guest interactions were characterized using X-ray diffraction and differential scanning calorimetry techniques. The resultant supramolecular hydrogel showed thixotropic properties, which are advantageous to drug delivery systems. In vitro release studies revealed that the supramolecular hydrogel exhibited faster drug release profiles in acidic conditions. The MTT assay demonstrated a synergistic cancer cell proliferation inhibition of DOX/8HQ-Glu mixture. In vitro cytotoxicity studies indicated excellent biocompatibility of the supramolecular hydrogel matrix, whereas the DOX/8HQ-Glu-loaded supramolecular hydrogel showed a sustained inhibition efficacy against cancer cells. The codelivery of hydrophobic anti-cancer drugs and hydrophilic anti-cancer drug glycoconjugates via a pH-responsive supramolecular hydrogel opens up new possibilities for the development of an effective cancer treatment based on the tumor-specific Warburg effect.